Internalisasi Nilai-Nilai Qur’ani Melalui Tradisi Yasinan dan Pembacaan Juz ‘Amma di Madrasah Ibtidaiyah Swasta Nurul Aflah Medan Labuhan - Humairoh Humairoh; Mardian Idris Harahap; Siti Ardianti (Yayasan Albahriah Jamiah Indonesia, 2026)
Qur’anic reading activities in madrasas often remain mere religious routines, whereas foundational Islamic education requires these practices to help students internalize values in their lives. This gap prompted a study into the traditions of Yasinan and the recitation of Juz’ Amma as religious practices with the potential to shape attitudes and behaviors. This research aims to analyze the implementation patterns of Yasinan and Juz’ Amma recitation, the mechanisms for internalizing Qur’anic values, the values ​​reflected in student behavior, and the relationships between the actors and the educational environment at MIS Nurul Aflah Medan Labuhan. The study employed a qualitative field research approach utilizing observation, interviews, and documentation, with data analyzed interactively through reduction, presentation, and conclusion drawing. The results indicate that Yasinan and Juz’ Amma recitation function as religious practices possessing a pedagogical structure characterized by activity regularity, guidance, habituation, repetition, role modeling, and collective experience. These mechanisms link Qur’anic recitation to the development of religiosity, discipline, responsibility, a sense of community, respect for the Qur’an, perseverance, and students’ moral and social behavior. The quality of internalization is influenced by teacher-student interactions, madrasa leadership, madrasa culture, and the educational environment, all of which reinforce consistent practice. These findings confirm that Qur’anic recitation can serve as a space for values ​​education when religious rituals are structured as consistent pedagogical experiences supported by role modeling and student engagement. Through this pattern, religious traditions acquire a transformative function, as values ​​are shaped via repeated experiences, social interaction, and the reinforcement of madrasa culture.